A novel extraction-free dual HiFi-LAMP assay for detection of methicillin-sensitive and methicillin-resistant Staphylococcus aureus - Xiuli Zhao; Yi Zeng; Beibei Yan; Yanping Liu; Yueqin Qian; Aiping Zhu; Yongjuan Zhao; Xiaoling Zhang; Chiyu Zhang; Zhenzhou Wan (Microbiology Spectrum, 2024)
ABSTRACTStaphylococcus aureus (S. aureus) is a leading cause of bacteremia and blood stream infections. Methicillin-resistant S. aureus (MRSA) that first appeared in 1961 often caused hospital-acquired infections (HAIs) and community-acquired infections (CAIs) and was associated with high mortality rate. Accurate and rapid point-of-care testing (POCT) of MRSA is crucial for clinical management and treatment of MRSA infections, as well as the prevention and control of HAIs and CAIs. Here, we reported a novel extraction-free dual HiFi-LAMP assay for discriminative detection of methicillin-susceptible S. aureus and MRSA. The dual HiFi-LAMP assay can detect 30 copies/reaction of nuc and mecA genes with detection limits of 147 and 158 copies per 25 µL reaction, respectively. A retrospective clinical evaluation with 107 clinical S. aureus isolates showed both sensitivity and specificity of 100%. A prospective clinical evaluation with 35 clinical samples revealed a specificity of 100% and a sensitivity of 92.3%. The dual HiFi-LAMP assay can detect almost all S. aureus samples (141/142; 99.3%) within 20 min, implying that the entire HiFi-LAMP assay (including sample process) can be completed within 40 min, extremely significantly shorter than 3–5 days by the traditional clinical microbial culture and antibiotic susceptibility testing. The novel extraction-free dual HiFi-LAMP assay can be used as a robust POCT tool to promote precise diagnosis and treatment of MRSA infections in hospitals and to facilitate surveillance of MRSA at hospital and community settings.IMPORTANCEMethicillin-resistant Staphylococcus aureus (MRSA) was associated with high mortality rate and listed as a “priority pathogen” by the World Health Organization. Accurate and rapid point-of-care testing (POCT) of MRSA is critically required for clinical management and treatment of MRSA infections. Some previous LAMP-based POCT assays for MRSA might be questionable due to their low specificity and the lack of appropriate evaluation directly using clinical samples. Furthermore, they are relatively tedious and time-consuming because they require DNA extraction and lack multiplex detection capacity. Here, we reported a novel extraction-free dual HiFi-LAMP assay for discriminative detection of MRSA and methicillin-susceptible S. aureus. The assay has high specificity and sensitivity and can be completed within 40 min. Clinical evaluation with real clinical samples and clinical isolates showed excellent performance with 100% specificity and 92.3%–100% sensitivity. The novel extraction-free assay may be a robust POCT tool to promote precise diagnosis of MRSA infections and facilitate surveillance of MRSA at hospital and community settings.